The Motivation of Adolescents in Preventing Gastritis Return in SMP Negeri 1 Karangjati, Karangjati District, Ngawi Regency - Arso Wibowo, Dodik; Adianti, Novita (Chakra Brahmanda Lentera Institute, 2021)
Background: Adolescent’s period is a time full of emotion and imbalance of mood swings and stress. Stress that is prolonged can be the trigger of Gastritis. Stress situation that has an impact on adolescents can increase the risk of recurrence so the adolescents need a strong motivation to increase the success in preventing the recurrence of Gastritis. The purpose of this study was to determine the motivation of adolescents in preventing recurrence of gastritis at SMP Negeri 1 Karangjati. Methods: The study design uses a descriptive, single variable that is adolescents’ motivation in preventing gastritis recurrence. The research population is 286 persons and a sample of 29 respondents so that use purposive sampling technique according to inclusion and exclusion criteria, research instrument uses a questionnaire sheet given to respondents by google form. The research was conducted from December 20 2020 to January 04, 2021. The data is analyzed using a percentage formula and interpreted quantitatively. Results: The result from 29 respondents, almost all of the respondents have strong motivation there are 24 respondents (83%) with strong motivation, 5 respondents (17%) with moderate motivation and no one of the respondents has weak motivation (0%). Conclusion: Adolescents’ motivation in preventing gastritis recurrence is influenced by for example sex, religion, residence, housemates, gastritis prevention familiarity, source of information, favorite food, hospitalization record, to the duration of having gastritis. It is hoped that adolescents can increase their motivation in preventing gastritis recurrence by finding more sources of information about how to implement a healthy diet.